KONDISI SANITASI PERALATAN DAN HIGIENE BAHAN MINUMAN TERHADAP KEBERADAAN BAKTERI Eschericia coli PADA ES TEH DI WARUNG KELURAHAN MULYOREJO, SURABAYA - Lisa Fitria Ningrum; Lilis Sulistyorini (Universitas Airlangga, 2019)
Food stall is one of catering services that provide food/beverages for the public. The handling of utensils and selecting good food and beveragesarethe efforts to prevent the presence of Escherichia coli on food and beverages in thefood stalls. The studyaims to describe the process of handling the utensils, selecting food ingredients, and testing the presence of Escherichia coli in iced tea. The method of this research was cross-sectional with 34 unit samples of food stalls in Mulyorejo Urban Village. The samples were inserted in plastic and tested in the laboratory with the Escherichia coli parameter. The interviews were conducted with the food vendorsregarding the sources of clean water, the washing process, handling the utensils, and the iced tea ingredients, such as drinking water, tea, sugar, and ice cubes. The analysis was conductedin a descriptive approach. The results showed that 24% of the samples were positive containing Escherichia coli. The sellers’ primary source of clean water was derived from the the Water Company (PDAM)by 82.3%. Furthermore, 67.6% of the samples used detergent/soap in the washing processwith two buckets,used to dip the utensils repeatedly. In terms of storing the utensils, 94.1% of the the utensils were glassware stored face down. The ingredients of iced tea consisted of boiled water (50%), obtained from the well and the Water Company (PDAM), the tea ingredients which had been registered in food control agency, the sugar which was not spoiled or smelled, and the ice cubes which were bought from the neighborhood area (88.2%). It isproven that Escherichia coli existed inthe iced tea due to the sanitary components of utensils and the hygiene of beverage ingredients did not meet the requirements. It is recommended that the guidance can be given to the vendors, especially in washing the utensils correctly and selectingthe beverage ingredients, such as water and ice cubes.